DESIGN, OPTIMIZATION (23FACTORIAL DESIGN), AND EVALUATION OF CARVEDILOL FAST DISSOLVING TABLETS BY EMPLOYING SOURSOP STARCH AS A NEW NATURAL SUPERDISINTEGRANT - MATTA, VASUDEVA REDDY; RADA, SANTOSH KUMAR (International Journal of Applied Pharmaceutics, 2025)
Objective: The study objective is to focus on the isolation of the Soursop Starch (SSS) from the fruit pulp of Annona muratica (Soursop) used as a natural super disintegrating agent in the carvedilol formulation of Fast-Dissolving Tablets (FDTs) using (23) factorial design. Methods: The SSS was isolated from the fruits of Annona muratica (Annonaceae family) by using sedimentation and centrifugation techniques. The physicochemical properties of the SSS were assessed. A direct compression method was employed to prepare Carvedilol Fast-Dissolving Tablets (C-FDTs). The factorial design was adopted at two levels (0 and 5 %) of superdisintegrant, and the dependent variables are SSS, psyllium husk, and Sodium Starch Glycolate (SSG). The Critical Quality Attributes (CQA) were measured for all eight formulations, including Disintegration Time (DT), Wetting Time (WT), % Drug Dissolved in 10 Min (PD10) and dissolution efficiency. The finished C-FDTs were evaluated for different test parameters like drug content, water absorption ratio, weight variation, hardness, dissolution, dissolution efficiency at 10 min, and stability studies for optimized formulation. Results: The isolated SSS was found to be insoluble in water and other inorganic solvents, and its swelling index, viscosity, bulk density, and tapped density were found to be satisfactory. The critical quality attributes like DT (22±1.38 sec), WT (24±0.58 sec), and PD10 (99.05±0.21 %) were found to be satisfactory for the optimized formulation (F2). The dissolution efficiency (F2) at a 10 min time point was found to be 44 times higher than that of the F1 formulation. Conclusion: C-FDTs were successfully designed and optimized by employing the SSS as a natural superdisintegrant which exhibited a better % of the drug release in 10 min with good DT, dissolution efficiency, and all other FDT characteristics.